Treatment gap for mental and behavioral disorders in Punjab - Rohit Garg; Bir Singh Chavan; Subhash Das; Sonia Puri; Arvind A. Banavaram; Vivek Benegal; Girish N. Rao; Mathew Varghese; Gopalkrishna Gururaj (Indian Journal of Psychiatry)
Background and Aims: There is no data on the treatment gap and health care utilization for mental disorders from Punjab. The present study reports on the same by using the data collected during the National Mental Health Survey. Settings and Design: Multisite, multistage, stratified, random cluster sampling study conducted in four districts, namely Faridkot, Moga, Patiala, and Ludhiana (for urban metro areas). Data were collected from October 2015 to March 2016. Materials and Methods: Mini International Neuropsychiatric Interview 6.0.0 and Adapted Fagerstrom Nicotine Dependence Scale were used to diagnose mental and behavioral disorders and tobacco use disorder, respectively. Pathways Interview Schedule of the World Health Organization was applied to persons having any disorder to assess treatment gap and health care utilization. Exploratory focused group discussions (FGDs) were conducted to understand the community perceptions regarding mental and behavioral disorders. Results: The treatment gap for mental and behavioral disorders was 79.59%, and it was higher for common mental disorders than severe mental disorders and higher for alcohol and tobacco use disorders as compared to opioid use disorders. The median treatment lag was 6 months. Only seven patients out of 79 were taking treatment from a psychiatrist, and the average distance traveled by the patient for treatment was 37.61 ± 45.5 km. Many attitudinal, structural, and other barriers leading to high treatment gaps were identified during FGDs in the community, such as stigma, poor knowledge about mental health, deficiency of psychiatrists, and distance from the hospital. Conclusions: Vertical as well as horizontal multisectoral integration is required to reduce the treatment gap and improve healthcare utilization. Increasing mental health literacy, providing high-quality mental health services at the primary-healthcare level and human resources development are the need of the hour.